2019
DOI: 10.1016/j.jcrs.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a patient-information video on the preoperative anxiety levels of cataract surgery patients

Abstract: Telephone: 075844392912 Abstract Purpose To assess whether a cataract surgery patient-information video reduces patients' preoperative anxiety levels. SettingLeeds Teaching Hospitals NHS Trust, UK. Design 3Prospective controlled trial of an intervention to reduce anxiety for first eye elective cataract surgery patients. MethodsA total of 200 patients attending for first eye elective cataract surgery were included in the study. The primary outcome measure was a questionnaire based upon the Amsterdam Pre-operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…Studies have shown that specific presurgical counseling improves patient knowledge about cataract surgery, 9 and decreases anxiety related to surgical procedures in various subspecialties, including ophthalmology. 4,8,10,[13][14][15]18 Technology has been used in a number of ways to increase the efficiency of the perioperative surgical visit for cataract surgery including educational videos and interactive computer-based tutorials. 19 Recent work by Tipotsch-Maca et al 10 and Zhang et al 13 suggest that a preoperative multimedia-assisted informed consent procedure for cataract surgery improves information retention.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that specific presurgical counseling improves patient knowledge about cataract surgery, 9 and decreases anxiety related to surgical procedures in various subspecialties, including ophthalmology. 4,8,10,[13][14][15]18 Technology has been used in a number of ways to increase the efficiency of the perioperative surgical visit for cataract surgery including educational videos and interactive computer-based tutorials. 19 Recent work by Tipotsch-Maca et al 10 and Zhang et al 13 suggest that a preoperative multimedia-assisted informed consent procedure for cataract surgery improves information retention.…”
Section: Discussionmentioning
confidence: 99%
“…It consisted of 20 items individually scored as either ( 1) not at all, (2) somewhat, (3) moderately, or (4) completely. The scale had ten reverse items (1,2,5,8,10,11,15,16,19,20).…”
Section: State-trait Anxiety Inventorymentioning
confidence: 99%
“…Although such a deficiency constitutes a limitation of this study, the technologysupported orientations foundin the literature aimed to relieve the concerns of inpatients in surgical-internal clinics before any procedure. 2,7,23,24,37,38,40 According to the results of these studies, the concerns of inpatients arise from uncertainties about the future or informational deficiencies regarding the procedures following their first-time admission to psychiatric clinics. These results are similar to those of this study.…”
Section: Patients Who Came On Mondays and Wednesdays Experimental Group (16)mentioning
confidence: 99%
See 2 more Smart Citations